6.30 TECHNICAL PARAMETERS OF THE ROADBED OF HIGH-SPEED RAILWAYS - Makhamajanov Shukhratjon Shavkat ugli, Umaraliev Shahjahan Mukhammadrozi ugli, Tadjibaev Sherzod Amirkulovich, Abdualiev Elyorbek Begali ugli. (Innovative technologies in construction Scientific Journal, 2024)
The article presents the technical parameters of the roadbed of high-speed highways according to several requirements and their design in size. The elements of the lower structure of the track used on the HSR and geomaterials to ensure the strength and stability of soils are described. Keywords: HSR, roadbed, embankment, excavation, soil. The roadbed of high-speed railways is subject to increased requirements in terms of its strength, stability, minimum deformability and durability [1.2.3.4]. The dimensions of the cross-section of the roadbed and, consequently, the volume of excavation work during the construction of the HSR are largely determined by the distance between the axes of the main tracks (inter-track). In order to reduce the aerodynamic impact of oncoming trains on each other, the distance between the axes of the main tracks on the HSR is increased. On conventional railways, it is about 4 m (in Russia, for example, 4.1 m), and on HSR it is assumed to be 4.7-4.8 m (in different countries). At the same time, the width of the main platform reaches 13 m or more. The roadbed of high-speed railways is arranged in the form of embankments or recesses and includes protective layers, the main body and drainage structures. for the construction of the roadbed on the HSR, rocky, clastic and gravelly soils are used. The best rock soils include granites, diorites, basalts and porphyrites. In addition to these, clay soils of solid and semi-solid consistency and sandy ones can be used. The elastic sediment of the main site of the roadbed under the action of a moving load should not exceed 1.5 mm. Technical requirements for reliable operation of the HSR web are ensured by high quality construction work, in particular, mandatory layer-by-layer filling and compaction of soil over the entire width of the roadbed, as well as constant quality control of work. The construction of the HSR roadbed is carried out using modern construction and road machinery. The set of machines, as part of the units that carry out the dumping of the earthwork during the construction of the HSR, includes bulldozers of various capacities, scrapers, dump trucks and tractors with dump trucks, graders, rollers, including vibratory, excavators and mechanical shovels (Fig.1).